Effect of Cooperative teaching Method on Students’ Academic Achievement in Basic Technology in Federal Government Colleges in Lagos State, Nigeria - Osuyi, S. O.; Dada, Babajide Oladimeji (NIU Journal of Social Sciences, 2020)
This study was designed to investigate the effect of cooperative learning methods on students’ academic achievement in basic technology in federal government colleges in Lagos state, Nigeria. Two purposes of the study were determined. Two research questions guided the study, while two null hypotheses were formulated and tested at 0.05 level of significant. The study employed a Quasi-experimental research design where pre and post-tests and non-equivalent groups were used in intact classes in order not to disrupt the smooth running of the classes as planned by the school authority. The sample used for the study was 123 Junior Secondary III students. The study used two intact classes where one of the schools served as experimental group, and the other one was used as control group. forty (40) multiple choice test items were developed and validated by three experts in the Department of Vocational and Technical Education, University of Benin, Benin City. The two intact classes were taught 4 topics in basic technology for a period of six weeks. Cooperative learning was used for teaching the experimental group while conventional method was used for the control group. Data collected after the treatment was analyzed using means and standard deviations to answer the research questions while t-test was used to test the hypotheses at 0.05 level of significance. From the data collected, it was found that students who were exposed to cooperative teaching performed better and had more knowledge of the subject than those who were taught using conventional teaching method. However, the results of the hypotheses tests revealed that the differences in the mean achievement scores of the two groups were significant. Hence, the study recommends that teachers should be adequately trained in the process of employing cooperative learning strategies for the effective teaching of basic technology in federal government colleges in Lagos State. Keywords: Cooperative learning method, Academic achievement, Basic technology